TREATMENT OF HYPERESTHESIA IN TEETH WITH" FLOUR - LUX" DRUG (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Tooth sensitivity is one of the most common patient complaints that drives patients to the dentist. Often, hypersensitivity is manifested as acute or moderate pain. It is influenced by various factors, they can be chemical (sour food), thermal (often cold water, ice). Ice cream, cold drinks or a sudden change of food can be for heating) and mechanical (toothbrush, toothbrush). Hypersensitivity of the hard tissues of the teeth often occurs when the structure of the teeth is damaged and hard tissues (caries process, increased sensitivity of the dental tissues, enamel erosion, follicular defects, etc.), periodontal diseases, and in some cases teeth without visible changes.